Pengaruh Pasteurisasi Terhadap Kandungan Vitamin C pada Aneka Kombucha Buah Tinggi Vitamin C: The Effect of Pasteurization on Vitamin C Level of Various Kombucha Fruits - Lailatus Sa'diyah; Vika Ayu Devianti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Kombucha is a fermented tea by bacteria and fungi called SCOBY for 7-14 days. The presence of microorganism in kombucha after fermentation process leads to additional fermentation. The longer preservation time, the more acid kombucha. The more acid kombucha affects the level of vitamin C. So, it is important to heat kombucha to reduce the number of microbes (pasteurization). The aim of this study is to know the effect of pasteurization on vitamin C level in various kinds of kombucha. After 7 days of kombucha fermentation, the kombucha heated for 15 minutes in 80oC then, the vitamin C level of kombucha measured with Spectro photometer UV-Vis in ? 265 wavelenght. The result shows that pasteurization (80oC) in 15 minutes does effects the vitamin c level of various kinds of kombucha. It decreased the level of vitamin C of kombucha before heating.